People's Republic of China : 2010 Article IV Consultation-Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
The Chinese government's macroeconomic policy response to the crisis has delivered positive results, and mitigated the impact of the global downturn on its economy. The challenge now is to sustain this strong growth performance while switching decisively to an economy that is powered by the Chinese consumer. This includes maintaining the fiscal stimulus, maintaining supervisory and regulatory vigilance, deploying prudential measures to counter unwarranted growth in real estate prices, liberalizing the financial system, building out China's social safety net, and capitalizing on urbanization, among others.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet